Ordinance of Government (Al-Ahkam al-Sultaniyah w’al Wilayat al-Diniyya) - Saiful Akmal (Puslatbang KHAN, 2013)
Book Title: The Ordinance of Government (Al-Ahkam al-Sultaniyah w'al Wilayat al-Diniyya)Author: Al-MawardiInterpreter: Prof. Dr. Wafaa H. WahbaPublisher: Garnet Publishing, United KingdomPrinted: 2010Pages: 301 pages